SAT0176 Long Term Successful Results of Medical (Steroid, Cyclophosphamide With/Without Interferon Alpha) and/or Endovascular Intervention for Aneurysm of Behcet Disease. (23rd January 2014) - Kalyoncu, U.; Peynircioglu, B.; Ertenli, I.; Er, G.; Er, E.; Karadag, O.; Kilic, L.; Bilgen, S.; Akdogan, A.; Cil, B.; Ozen, S.; Kiraz, S.
Abstract : Background: Behcet disease (BD) can present with arterial and/or venous involvement. Rupture of aneurysms is a major cause of mortality in BD. We lack evidence based data for the treatment/management of aneurysms. Objectives: The objective of these study was to assess to management of aneurysms in BD. Methods: Central hospital database record all reports of CT/MRI since 1999 were reviewed. First, we searched "aneurysm" as a key word in patients who have been seen recorded at least once time in the database of rheumatology clinics, 655 patients were found. Subsequently CT/MRI and drug reports were searched for BD. At the first assessment 32 patients were identified to have aneurysms. Files were reevaluated for fulfilling of BD criteria and 3 patients were excluded. Five were not followed regularly by the rheumatology department and 2 had cerebral aneurysms. The remaining 23 patients (74% male) were assessed for demographics, clinical history, imaging, detailed medical and surgical management. Results: The mean age, mean disease onset age and median follow-up duration were 39±11 years, 27±8 years and 48 (0-263) months respectively. Features of BD included oral aphtoses 23 (100%), genital ulcers 17 (74%), acne 10 (43%), erythema nodosum 8 (35%), joint 9 (39%), uveitis 6 (26%), neurological 4 (17%), pathergy 5 (22%) and fever 13 (56%). Fifteen patients (65%) also had venous thrombosis. Distribution area of aneurysms were pulmonary in 9 (39%), abdominal aorta in 6 (26%), iliac artery in 5 (22%), and one patient each (4%) had internal carotid, coronary, tibial, popliteal, and subclavian artery. Only 3 of the 23 (13%) patients had received steroid or cyclophosphamide (CYC) before the detection of the aneurysm. Thirteen of the 23 (56%) patients received pulse/oral steroid, pulse CYC with interferon alpha (IFN-α) and 5 patients (20%) received pulse/oral steroid, pulse CYC without IFN-α. The remaining 6 patients were given either only IFN-α or azatiopurine plus oral steroids. Median duration of pulse steroid and CYC was 15 (2-60) months, and median duration of IFN-α was 24 months (2-110). Seven of 25 (28%) patients were already on anti-coagulant treatment before aneurysm. Fourteen patients (61%) received prophylactic (11 of 14) or therapeutic (3 of 14) anticoagulant therapy for venous thrombosis after the detection of aneurysm. No major bleeding was seen due to anticoagulant treatment. Embolization was performed for 12 (52 %) patients. Median follow-up duration after embolization was 49 months (2-246). Emerging causes of embolization was bleeding 5 (4 hemoptysis, 1 gastrointestinal). Seven patients underwent embolization because of the large size of the aneurysm. Two patients (8%) died (1 abdominal aneurysm rupture and 1 cerebrovascular accident plus hemoptysis) during follow-up. Conclusions: Mortality rate among our BD patients with aneurysm was lower than that reported in the literature. Effective endovascular intervention has surely improved the outcome of our patients. On the other hand since more than half of our patients received CYC along with IFN-α, this regimen may be a promising alternative in the treatment of these patients Disclosure of Interest: None Declared